The clinical utility of next generation sequencing in endometrial cancer: focusing on molecular subtyping and lynch syndrome - Guo, Yongzhen; Yan, Guangwei; Zhang, Pei; Liu, Yixuan; Zhao, Chengquan; Zeng, Xianxu (Frontiers in Genetics, 2024)
Objective To investigate the clinical utility of Next Generation Sequencing (NGS) in molecular typing of endometrial carcinoma and its combined screening for Lynch Syndrome (LS). Methods 90 patients diagnosed with endometrial carcinoma (EC) and receiving treatment at the Third Affiliated Hospital of Zhengzhou University between March 2022 and December 2023 were included in this study. Molecular typing and germline evaluation for LS were conducted using NGS on the Illumina platform. A retrospective analysis was performed to examine the clinical pathological characteristics, molecular mutation spectrum, and LS screening outcomes among patients with four distinct molecular subtyping categories. Results Among the 90 cases of EC, 11 cases (12.2%) of POLE mut type, 19 cases (21.1%) of MMRd type, 6 cases (6.7%) of p53 abn type, and 54 cases (60%) of NSMP type were detected, with detailed analysis of their respective molecular characteristics. LS screening identified 9 cases (10%) of pathogenic germline mutations in MMR genes, including 3 cases of MLH1 germline mutations, 2 cases of PMS2, 2 of MSH2, and 2 of MSH6. Of the 9 LS patients, 7 were MMRd type and 2 NSMP type, with 7 cases showing abnormal MMR protein expression. Additionally, 6 cases with germline variants of uncertain significance in MMR genes were detected, including 2 MLH1, 1 MSH6, 2 MSH6, 1 PMS2, and 1 EPCAM. Conclusion NGS enables precise molecular typing of endometrial carcinoma through the identification of mutations in the POLE, TP53, and MMR genes. Conducting germline mutation testing for MMR genes in all patients with endometrial carcinoma can effectively prevent instances of overlooked LS diagnoses. Nevertheless, the extensive expenses associated with NGS necessitate additional validation and investigation before its clinical implementation can be fully endorsed.